CARACTERIZACIÓN DE LA PREPARACIÓN PEDAGÓGICA DE LOS DOCENTES DE INGENIERÍA INDUSTRIAL DEL INSTITUTO TECNOLÓGICO DE VERACRUZ. MÉXICO - Mejía Correa , Juan José Alberto; Bermúdez Sarguera , Rogelio; Mejía Pérez , Juan Francisco; Pentón Quintero, Aylín (Revista Minerva, 2023)
In this article, a methodological proposal is focused on for the characterization of the pedagogical preparation of teachers at the Technological Institute of Veracruz, in Mexico. Therefore, the objective pursued with this research is limited to the characterization of the level of pedagogical preparation of the teachers of the Industrial Engineering career of the aforementioned institute. The study is carried out through two subjects, contained in the curriculum of the curriculum, namely “Quality Control” and “Quality Management”. Expert surveys and unstructured interviews were predominantly used as effective methods in collecting information, as well as analysis and synthesis and the system approach as methods aimed at processing the collected information. Although teachers are in charge of planning and developing professional teaching praxis, they are unaware of the science of didactics and, with it, the methodological work aimed at improving the training of students in an efficient and effective way.